Associations of serum folate and vitamin B12 levels with all-cause mortality among patients with metabolic dysfunction associated steatotic liver disease: a prospective cohort study - Zhu, Jiaxin; Liao, Xinyi; Du, Lei; Lv, Pengju; Deng, Jian (Frontiers in Endocrinology, 2024)
Introduction: Serum folate and vitamin B12 levels correlate with the prevalence of fatty liver disease, but it is not clear how they affect mortality. Therefore, this study aimed to investigate the association of serum folate and vitamin B12 concentrations with all-cause mortality in individuals with metabolic dysfunction-associated steatotic liver disease (MASLD). Methods: MASLD subjects were from the Third National Health and Nutrition Examination Survey (NHANES III) in the United States, and mortality follow-up data were obtained by linkage to death records from the National Death Index. Multivariable Cox proportional regression models and restricted cubic spline (RCS) models were used to evaluate the association of serum folate/vitamin B12 with all-cause mortality in the MASLD population. Results: 3,636 and 2,125 MASLD individuals were included in the analyses related to serum folate and vitamin B12, respectively. During a follow-up period of more than 20 years, the RCS models demonstrated significant nonlinear associations of both serum folate (P <0.001) and vitamin B12 (P =0.016) with all-cause mortality in MASLD. When their serum concentrations were below the median level, the risk of all-cause mortality decreased with increasing concentration, reaching a lowest risk around the median level, and then leveled off. In the multivariable cox regression model, for vitamin B12, the risk of all-cause mortality was reduced by 42% and 28% in the third and fourth quartile groups, respectively, compared with the lowest quartile group (hazard ratio [HR]=0.58, 95% CI: 0.39-0.86, P =0.008; HR =0.72, 95% CI: 0.54-0.96, P=0.026, respectively). For folate, the risk of all-cause mortality was reduced by 28% in the third quartile compared with the lowest quartile (HR =0.72, 95% CI: 0.57-0.91, P =0.005). Conclusion: This longitudinal cohort study suggests that low serum folate and vitamin B12 levels in patients with MASLD are significantly associated with an elevated risk of all-cause mortality.